1981
DOI: 10.1083/jcb.89.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various hepatic membrane fractions on microtubule assembly-with special emphasis on the role of membrane phospholipids.

Abstract: This report describes an interaction between rat brain microtubule protein and various hepatic fractions in vitro . Purified preparations of Golgi membranes, plasma membranes, rough and smooth endoplasmic reticulum, nuclear membranes, and mitochondria were obtained from the livers of 200-g rats . Several concentrations of fresh or sonicated frozen membranes were incubated with twice-cycled rat brain microtubule protein in a microtubule assembly buffer for 60 min at 30°C. Changes in microtubule assembly were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Membrane-or phospholipid-associated tubulin has been reported (Bhattacharyya and Wolff, 1976;Klausner et al, 1981;Kumar et al, 1981;Reaven and Azhar, 1981;Regula et al, 1986;Caron and Berlin, 1987). It appeared that this "membrane" tubulin was similar to the soluble form (Bhattacharyya and Wolff, 1976;Stephens, 1977).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Membrane-or phospholipid-associated tubulin has been reported (Bhattacharyya and Wolff, 1976;Klausner et al, 1981;Kumar et al, 1981;Reaven and Azhar, 1981;Regula et al, 1986;Caron and Berlin, 1987). It appeared that this "membrane" tubulin was similar to the soluble form (Bhattacharyya and Wolff, 1976;Stephens, 1977).…”
Section: Discussionmentioning
confidence: 84%
“…Phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ) as well as the second messenger IP 3 can bind to certain PIP 2 -binding protein domains (Ferguson et al, 1995;Kavran et al, 1998), and the negative charge of these molecules was presumed responsible for such interaction. The anionic phospholipid constituents of hepatic membranes have also been reported to account for membrane binding of brain microtubule protein and inhibition of assembly (Reaven and Azhar, 1981). A hydrophobic interaction of tubulin (Andreu, 1986) with the uncharged phospholipid phosphatidylcholine at the lipid phase transition temperature Kumar et al, 1981) has been found as well.…”
Section: Specific Interaction With Pip 2 Decreases Tubulin Polymerizamentioning
confidence: 80%
See 1 more Smart Citation
“…These fragments are sometimes empty but usually have a loose fibrillar interior similar to the microvillus cavities seen in the intact tissue: more certain identification came from the fact that many of these structures still retained the double membranes with fibrillar connections (see arrows) that are seen so clearly in Figs. [8][9][10]. By taking advantage of the characteristic appearance of these membrane fragments, we were able to quantitatively assess their content in the special mitochondrial fraction and their degree of labeling with radioactive HDL (Table III).…”
Section: Methodsmentioning
confidence: 99%
“…Different sets of ARGs from each sample were developed at weekly intervals until one set proved to have sufficient grains for quantification. At this point, 10 nucleated cells (chosen at random) of each of three blocks per sample were photographed at a low magnification (X 4,000) so as to include an image of the entire cell: such micrographs were printed on 11 X 14 sheets of paper. Each exposed grain that was determined to be associated with the LC in question was delineated with a tightfitting circle: the number of grains varied from -15-30/cell.…”
Section: Methodsmentioning
confidence: 99%